1998
DOI: 10.1097/00004647-199810000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Therapeutic Window for Ischemic Brain Damage Caused by Delayed Caspase Activation

Abstract: Apoptotic cell death is prominent in neurodegenerative disorders, such as Alzheimer's disease and Huntington's disease, and is found in cerebral ischemia. Using a murine model of delayed cell death, we determined that cleavage of zDEVD-amino-4-trifluoromethyl coumarin (zDEVD-afc) in brain homogenate, a measure of caspase activation, increased initially 9 hours after brief (30 minutes) middle cerebral artery occlusion along with caspase-3p20 immunoreactive cleavage product as determined by immunoblotting. zDEVD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
98
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 198 publications
(107 citation statements)
references
References 30 publications
8
98
0
1
Order By: Relevance
“…Caspase-3 is also the most abundant cysteine aspartase expressed in adult rodent brain and caspase-3-like enzyme activity and activated caspase-3 subunits are detected in ischemic tissues by immunoblotting and immunohistochemistry (6,7). Treatment with peptide-based caspase inhibitors protects brain from mild ischemic injury and improves neurological deficits (8)(9)(10). We extend the findings above by studying ischemic mechanisms in caspase-3 Ϫ/Ϫ brain in vivo and in vitro.…”
supporting
confidence: 52%
“…Caspase-3 is also the most abundant cysteine aspartase expressed in adult rodent brain and caspase-3-like enzyme activity and activated caspase-3 subunits are detected in ischemic tissues by immunoblotting and immunohistochemistry (6,7). Treatment with peptide-based caspase inhibitors protects brain from mild ischemic injury and improves neurological deficits (8)(9)(10). We extend the findings above by studying ischemic mechanisms in caspase-3 Ϫ/Ϫ brain in vivo and in vitro.…”
supporting
confidence: 52%
“…31 Moreover, caspase inhibitors are neuroprotective in in vivo and in vitro models of ischemia. [32][33][34][35][36] We have, however, recently found that caspase activation also contributes to endogenous pathway which can protect against ischemic and excitotoxic injury.…”
Section: Caspase Activation In Neuroprotection/ischemic Tolerancementioning
confidence: 99%
“…Caspase 3 activation has been detected following focal (and global) ischaemic insults to the brain [14][15][16][17][18][19] where it coincides with areas of enhanced apoptotic cell death 14 and treatment with caspase 3 inhibitors has been reported to reduce infarct size following MCA occlusion. 14,[56][57][58] Moreover, studies in caspase 3-deficient mice indicate that these animals are relatively resistant to ischaemic insults with smaller lesions than their WT littermates.…”
Section: Discussionmentioning
confidence: 99%
“…10 The decreased apoptosis observed in the brain suggested a critical role for caspase 3 in the development of the central nervous system. Caspase 3 has also been implicated in cell death following a number of neurodegenerative insults including global ischaemia, 12,13 focal ischaemia, [14][15][16][17][18][19] transient ischaemia of the spinal cord, 20 neonatal cerebral hypoxia-ischaemia, [21][22][23] traumatic brain injury, [24][25][26] Alzheimer's disease, [27][28][29] Huntington's disease, [30][31][32] and Parkinson's disease. [33][34][35][36][37] It was therefore hypothesized that overexpression of caspase 3 may sensitize the animal to normal (physiological) apoptotic processes that occur during development and natural ageing and confer particular susceptibility to neurodegenerative insults.…”
Section: Introductionmentioning
confidence: 99%